2002
DOI: 10.1002/em.10102
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic risk and oxidative DNA damage in workers exposed to antimony trioxide

Abstract: The growing use of antimony (Sb) compounds in industry and the consequent increase in the number of exposed workers make it important to carry out a health risk assessment. The main goal of this study was to assess the genotoxicity of Sb(2)O(3) in occupationally exposed workers. Genotoxicity was evaluated by the sister chromatid exchange (SCE) and micronucleus tests, and the enzyme (Fpg)-modified comet assay. In addition, antimony exposure levels were established by environmental monitoring with personal air s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…However, there have been few studies attempting to clarify the mechanism of antimony. With regard to humans, Cavallo et al showed that oxidative DNA damage might be involved in the genotoxicity of antimony in a study including 23 male workers who handled materials containing antimony 16) . In addition, antimony trioxide was classified as possibly carcinogenic to humans (Group 2B), but antimony trisulfide was not classifiable as to its carcinogenicity to humans (Group 3) by IARC 17) , based on animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies attempting to clarify the mechanism of antimony. With regard to humans, Cavallo et al showed that oxidative DNA damage might be involved in the genotoxicity of antimony in a study including 23 male workers who handled materials containing antimony 16) . In addition, antimony trioxide was classified as possibly carcinogenic to humans (Group 2B), but antimony trisulfide was not classifiable as to its carcinogenicity to humans (Group 3) by IARC 17) , based on animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The association of MDA as biomarker of lipid peroxidation and PCDD/Fs were significant, because PCDD/Fs are lipid soluble. Oxidative damage may inhibit cell-mediated immunity toward infectious agents, exacerbate respiratory allergy, cause DNA damage, and under longterm exposure, induce the development of tumors [41][42][43][44][45] .…”
Section: Health Assessment With Biomarkers Of Oxidative Damagementioning
confidence: 99%
“…This exposure can generate toxic health effects, which has been observed in other cases of human exposure to Sb, such as kidney, lung and skin damage (Roper WL. U.S. Public Health Service, 1992;Cavallo et al, 2002). The indiscriminate use of Sb drugs against leishmaniasis has similar adverse effects and causes cardiotoxicity and pancreatitis (Croft et al, 2006;Oliveira et al, 2011;Sundar and Chakravarty, 2010).…”
Section: Introductionmentioning
confidence: 99%